2005
DOI: 10.1016/j.lfs.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of capsaicin-sensitive afferent nerves affects insulin response during an intravenous glucose tolerance test

Abstract: We investigated the role of sensory nerves in glucose tolerance in conscious Wistar rats neonatally treated with neurotoxin capsaicin or vehicle. Intravenous glucose tolerance tests (IVGTT, 150, 300 and 450 mg in 30 min) were performed to measure glucose tolerance, and glucose, insulin and glucagon levels were measured. Higher glucose concentration resulted in a greater insulin response in both capsaicin- and vehicle-treated rats. However, glucose-stimulated insulin secretion was attenuated in capsaicin-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
4
17
0
2
Order By: Relevance
“…Thus, whereas the IVGTT caused similar increments in blood glucose levels in CAP and VEH rats, the plasma insulin response was markedly reduced in CAP rats relative to that in VEH-treated controls. These data confirm our previous findings in non-fasted CAP and VEH rats challenged with different glucose loads, yielding similar dose-dependent elevations in blood glucose levels, but with much lower plasma insulin responses in CAP rats relative to those seen in VEH rats [17]. While the reduced glucose-mediated insulin response in CAP rats might be the result of absence of tonic activation of vagal afferents by gut hormones [17,18], one implication of these findings is that CAP rats are more insulin-sensitive than VEH controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, whereas the IVGTT caused similar increments in blood glucose levels in CAP and VEH rats, the plasma insulin response was markedly reduced in CAP rats relative to that in VEH-treated controls. These data confirm our previous findings in non-fasted CAP and VEH rats challenged with different glucose loads, yielding similar dose-dependent elevations in blood glucose levels, but with much lower plasma insulin responses in CAP rats relative to those seen in VEH rats [17]. While the reduced glucose-mediated insulin response in CAP rats might be the result of absence of tonic activation of vagal afferents by gut hormones [17,18], one implication of these findings is that CAP rats are more insulin-sensitive than VEH controls.…”
Section: Discussionsupporting
confidence: 91%
“…These data confirm our previous findings in non-fasted CAP and VEH rats challenged with different glucose loads, yielding similar dose-dependent elevations in blood glucose levels, but with much lower plasma insulin responses in CAP rats relative to those seen in VEH rats [17]. While the reduced glucose-mediated insulin response in CAP rats might be the result of absence of tonic activation of vagal afferents by gut hormones [17,18], one implication of these findings is that CAP rats are more insulin-sensitive than VEH controls. This idea is in agreement with the findings of Koopmans et al [11], who observed increased whole body insulin action in CAP rats under euglycemic hyperinsulinemic clamp conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Karlsson et al [42] found that sensory denervation results in increased glucose tolerance in mice due in part to a potentiated insulin response to glucose. In contrast, van de Wall et al [105] reported that glucose-stimulated insulin secretion is attenuated in Wistar rats that were treated with capsaicin, even though their glucose levels did not differ. Thus, the role of TRPV1 in physiological states is not fully understood.…”
Section: Trp Channels and Diabetesmentioning
confidence: 87%
“…27,28 Furthermore, the pancreas is more susceptible to oxidative stress than other organs because of its lower antioxidative system. 29 Baechu kimchi contains several ingredients in addition to Chinese cabbage, such as onion, ginger, garlic, and red chili, which have proven hypolipidemic, 30 hypoglycemic, [31][32][33] insulinotropic, 34,35 and antidiabetic effects. [35][36][37][38] Additionally, as a salted-fermented food, kimchi is a rich source of various strains of lactic acid bacteria, which have several beneficial effects on health.…”
Section: Discussionmentioning
confidence: 99%